The pragmatic foundations of communication: An action-oriented model of the origin of language - Adornetti, Ines; Ferretti, Francesco (Theoria et Historia Scientiarum, 2015)
In this paper we propose an action-oriented model of language origins that is compatible with the embodied perspective of mind. Specifically, we maintain that a crucial issue for the investigation of the origin of human communication is how language is grounded in the context. In support of such a proposal, we maintain that: a) the grounding of language is tied to a specific aspect of the embodied mind, namely the aspect that emphasizes the embedded character of cognition; b) the emphasis posed on this particular character fits well with a model of language origins founded on gesture. The connection of embedded cognition and the gestural model allows us to propose an explanation of language origin capable of overcoming the problems in the classical symbolic framework of cognitive sciences.